Educational Applications to Improve Cognitive Development in Early Children: a Review of Educational Psychology - Sappaile, Baso Intang (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Educational applications for early childhood (PAUD) are very important for growing children's cognitive abilities. Cognitive development in early childhood develops quickly and dynamically and can be influenced by many factors, such as the environment, opportunities and their own cognitive style. Cognitive development in early childhood includes thinking, language and behavioral abilities related to understanding, consideration, information processing, problem solving, deliberateness and belief. This research was conducted with the aim of creating educational applications that can improve the cognitive abilities of young children through various fun educational activities. Cognitive Development in Early Childhood: A Review of Educational Psychology is to use a quantitative method. The data obtained by researchers was obtained from the results of distributing questionnaires. The distribution of questionnaires carried out by researchers was carried out online using Google From software. The results of research on educational applications to improve the cognitive development of early childhood can show several things related to educational psychology, such as, experience-based learning methods can encourage children's creativity. From this research, researchers can conclude that educational applications to improve cognitive development in early childhood are very effective for use in the learning process.